Tracking fibrosis in myeloproliferative neoplasms by CCR2 expression on CD34+ cells - Pozzi, Giulia; Carubbi, Cecilia; Gobbi, Giuliana; Tagliaferri, Sara; Mirandola, Prisco; Vitale, Marco; Masselli, Elena (Frontiers in Oncology, 2022)
In myeloproliferative neoplasm (MPNs), bone marrow fibrosis - mainly driven by the neoplastic megakaryocytic clone - dictates a more severe disease stage with dismal prognosis and higher risk of leukemic evolution. Therefore, accurate patient allocation into different disease categories and timely identification of fibrotic transformation are mandatory for adequate treatment planning. Diagnostic strategy still mainly relies on clinical/laboratory assessment and bone marrow histopathology, which, however, requires an invasive procedure and frequently poses challenges also to expert hemopathologists. Here we tested the diagnostic accuracy of the detection, by flow cytometry, of CCR2+CD34+ cells to discriminate among MPN subtypes with different degrees of bone marrow fibrosis. We found that the detection of CCR2 on MPN CD34+ cells has a very good diagnostic accuracy for the differential diagnosis between “true” ET and prePMF (AUC 0.892, P<0.0001), and a good diagnostic accuracy for the differential diagnosis between prePMF and overtPMF (AUC 0.817, P=0.0089). Remarkably, in MPN population, the percentage of CCR2-expressing cells parallels the degree of bone marrow fibrosis. In ET/PV patients with a clinical picture suggestive for transition into spent phase, we demonstrated that only patients with confirmed secondary MF showed significantly higher levels of CCR2+CD34+ cells. Overall, flow cytometric CCR2+CD34+ cell detection can be envisioned in support of conventional bone marrow histopathology in compelling clinical scenarios, with the great advantage of being extremely rapid. For patients in follow-up, its role can be conceived as an initial patient screening for subsequent bone marrow biopsy when disease evolution is suspected.